Resolution of AV block after ablation for atrial fibrillation - Glassy, Matthew (J Atr Fibrillation, 2017)
We report a case with complete atrioventricular block (AVB) present both during sinus rhythm and with atrial fibrillation (AF). He had declined pacemaker placement and opted for ablation for the symptomatic AF. He underwent staged hybrid approach with video-assisted thoracoscopic surgical maze (VATS) followed by endocardial ablation. VATS included ganglionic plexi cauterization. One month after the endocardial procedure, he had complete resolution of AF and AVB and remains so at 18 months follow up. We discuss possible abolition of vagal input for this improvement in AV conduction.